Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10068-012-0098-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influence on phenolic-mediated antihyperglycemic properties of Canadian sugar and red maple leaves using in vitro assay models

Abstract: Red and sugar maple leaves collected in the summer and fall from Canada, were evaluated for phenolic content, antioxidant, α-glucosidase, and α-amylase inhibitory activities variation. The phenolic contents of summer red maple leaves (RML-S) and summer sugar maple leaves (SML-S) were higher than red and sugar maple leaves collected in fall (RML-F and SML-F, respectively). HPLC analyses showed differences in phenolic compounds present in the SML samples compared to the RML samples. The extracts were assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
2
11
0
Order By: Relevance
“…It is well documented that phenolic phytochemicals have alpha-glucosidase inhibitory activity that depends on the phenolic profile (Kwon et al 2006(Kwon et al , 2007Apostolidis et al 2012). A recent study reported that cinnamon extract has shown non-PAC-dependent rat alpha-glucosidase inhibitory activity (Kang et al 2014).…”
Section: Proanthocyanidin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that phenolic phytochemicals have alpha-glucosidase inhibitory activity that depends on the phenolic profile (Kwon et al 2006(Kwon et al , 2007Apostolidis et al 2012). A recent study reported that cinnamon extract has shown non-PAC-dependent rat alpha-glucosidase inhibitory activity (Kang et al 2014).…”
Section: Proanthocyanidin Contentmentioning
confidence: 99%
“…Therefore, inhibition of alpha-glucosidases (sucrase and maltase) can be an effective strategy to reduce the glucose absorption in the digestive tract (Krentz and Bailey 2005). It has been reported that certain natural products are potentially good inhibitors of carbohydrate-hydrolyzing enzymes with their effect being attributed to the unique phenolic phytochemicals (Kwon et al 2006(Kwon et al , 2007Apostolidis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Attractively, a series of novel compounds, such as maplexin A-F, have been isolated and identified by means of chromatography techniques and elucidation of NMR and ESIMS data . Meanwhile, maple extracts were evidenced to show good antiproliferative (González-Sarrías et al, 2012a,b), antiinflammatory (Nahar et al, 2014), anticancer (González-Sarrías et al, 2013), antihyperglycemic (Apostolidis et al, 2012), and antioxidant activities (Zhang et al, 2015b), especially the potential in preventing diabetes and diabetic complications (Apostolidis et al, 2012;Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ginnalins A ( 8 ), B ( 3 ), and C ( 4 ) represent over 75% of the total phenolic content with 41.4%, 11.0%, and 24.4%, respectively. These compounds have already been reported to be the major phenolic compounds identified in red maple leaves, but their concentrations were not reported . Moreover, the antioxidant capacity of these compounds against DPPH · free radical has been evaluated previously .…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have already been reported to be the major phenolic compounds identified in red maple leaves, but their concentrations were not reported. [11] [27] Moreover, the antioxidant capacity of these compounds against DPPH Á free radical has been evaluated previously. [10] Interestingly, ginnalin A (EC 50 = 17.74 lM), ginnalin B (EC 50 = 32.70 lM), and ginnalin C (EC 50 = 30.49 lM) have all shown a better antioxidant activity than ascorbic acid (EC 50 = 71.02 AE 1.61 lM), a well-known antioxidant standard.…”
Section: Quantitative Analysis Of Phenolic Constituentsmentioning
confidence: 99%